Device security features supporting a distributed shared memory system - MENON AMITABH; ZBICIAK JOSEPH R. M (2014)
A memory management and protection system that incorporates device security features that support a distributed, shared memory system. The concept of secure regions of memory and secure code execution is supported, and a mechanism is provided to extend a chain of trust from a known, fixed secure boot ROM to the actual secure code execution. Furthermore, the system keeps a secure address threshold that is only programmable by a secure supervisor, and will only allow secure access requests that are above this threshold.